Design, synthesis, and biological evaluation of NAD(P)H: quinone oxidoreductase (NQO1)-targeted oridonin prodrugs possessing indolequinone moiety for hypoxia-selective activation - Xu, Shengtao; Yao, Hong; Pei, Lingling; Hu, Mei; Li, Dahong; Qiu, Yangyi; Wang, Guangyu; Wu, Liang; Yao, Hequan; Zhu, Zheying; Xu, Jinyi (Elsevier, 2017)
The enzyme NQO1 is a potential target for selective cancer therapy due to its overexpression in certain hypoxic tumors. A series of prodrugs possessing a variety of cytotoxic diterpenoids (oridonin and its analogues) as the leaving groups activated by NQO1 were synthesized by functionalization of 3-(hydroxymethyl)indolequinone, which is a good substrate of NQO1. The target compounds (29a-m) exhibited relatively higher antiproliferative activities against NQO1-rich human colon carcinoma cells (HT-29) and human lung carcinoma (A549) cells (IC50 ¼ 0.263e2.904 mM), while NQO1-defficient lung adenosquamous carcinoma cells (H596) were less sensitive to these compounds, among which, compound 29h exhibited the most potent antiproliferative activity against both A549 and HT-29 cells, with IC50 values of 0.386 and 0.263 mM, respectively. Further HPLC and docking studies demonstrated that 29h is a good substrate of NQO1. Moreover, the investigation of anticancer mechanism showed that the representative compound 29h affected cell cycle and induced NQO1 dependent apoptosis through an oxidative stress triggered mitochondria-related pathway in A549 cells. Besides, the antitumor activity of 29h was also verified in a liver cancer xenograft mouse model. Biological evaluation of these compounds concludes that there is a strong correlation between NQO1 enzyme and induction of cancer cell death. Thus, this suggests that some of the target compounds activated by NQO1 are novel prodrug candidates potential for selective anticancer therapy.